Do free trade agreements facilitate FDI spillover effects on domestic firms? Empirical evidence from Oman - Ashraf Mishrif; Asharul Islam Khan (Economies, 2024)
This paper underlines the significance of free trade agreements in attracting foreign direct investment and their impact on the operational capacities of local firms in host countries. It argues that free trade agreements do not only eliminate barriers to trade, but they also increase the size of the regional market and improve the business environment, making it more attractive to foreign direct investment, along with all the attributes and spillover effects associated with it. While determining the type of spillover effects of foreign direct investment associated with Oman's trade agreements, this paper uses the Kruskal-Wallis H-test and 438 samples from companies surveyed between 1 August and 31 October 2023 to assess the impact of spillovers on the performance of the surveyed companies. The results reveal that technology transfer, knowledge transfer, labour productivity, product efficiency, capital investments, and job creation have positive effects on the firms' operational capacities, with technology transfer having the highest impact (27%), followed by labour productivity and job creation (18%). The spillover effects are almost the same for company size and percentage of ownership. They also identified manufacturing and tourism as priority sectors and the availability of a skilled workforce as a major challenge. These findings make original contribution to the field as this is probably the first study to produce a firm-level analysis of spillover effects of foreign direct investment and trade agreements in the context of Oman and the wider Gulf region. The paper concludes with practical implications for policy makers when negotiating trade agreements and designing investment policies to optimize spillover effects on the performance of their domestic firms.
Keywords: 330; foreign direct investment; free trade agreements; Oman; spillover effects; technology and transfer